2020
DOI: 10.1186/s11671-020-3293-3
|View full text |Cite
|
Sign up to set email alerts
|

Co-delivery of Dacarbazine and All-Trans Retinoic Acid (ATRA) Using Lipid Nanoformulations for Synergistic Antitumor Efficacy Against Malignant Melanoma

Abstract: Malignant melanoma is a highly aggressive skin cancer responsible for 80% of mortality, and the overall median survival in patients with metastatic melanoma is only 6-9 months. Combination treatment through the simultaneous administration of dual drugs in a single nanocarrier has been demonstrated to be elegant and effective in combatting cancer. Herein, we employ a combination therapy based on dacarbazine (DBZ), FDA approved drug for melanoma and all-trans retinoic acid (ATRA), promising anticancer agents loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…They showed that the simultaneous delivery of ATRA and dacarbazine resulted in significant inhibition of colony formation and cell proliferation in B16F10 melanoma cells. Similar to our study, they showed that the combination of ATRA and dacarbazine inhibited the melanoma cells at the sub-G0 phase [24].…”
Section: Discussionsupporting
confidence: 91%
“…They showed that the simultaneous delivery of ATRA and dacarbazine resulted in significant inhibition of colony formation and cell proliferation in B16F10 melanoma cells. Similar to our study, they showed that the combination of ATRA and dacarbazine inhibited the melanoma cells at the sub-G0 phase [24].…”
Section: Discussionsupporting
confidence: 91%
“…However, the application of ATRA in solid tumors remains to be explored. RA can inhibit tumor cell proliferation in melanoma ( Edward and MacKie, 1989 ; Zhang and Rosdahl, 2005 ; Li and Han, 2020 ) and promote immune surveillance in breast cancer, colorectal cancer, and melanoma by influencing the metabolism of MDSCs, upregulating genes related to immune response, and supporting the survival of tumor-specific CD8 + T cells ( Guo et al, 2012 ; Paroni et al, 2020 ; Sun et al, 2020 ). Conversely, RA treatment was also reported to benefits tumor progression in sarcoma and chronic lymphocytic leukemia (CLL) by promoting the pro-tumoral differentiation of intertumoral monocytes in sarcoma and increasing CD38 expression in CLL cells ( Chen et al, 2018 ; Devalaraja et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The combination strategy is one of the possible solutions that can overcome the resistance of melanoma cells to conventional therapy. Li and Han [54] have shown that a combination of dacarbazine and all-trans retinoic acid, loaded in lipid nanoformulations, is able to reduce B16F10's colony formation ability, whereas dacarbazine alone shows a limited ability to inhibit colony formation. In several studies, the colony-forming effect of kinase inhibitors was assessed by clonogenic assay.…”
Section: Pharmacology 221 Anticancer Activitymentioning
confidence: 99%